Description of the larva of Caucasian species Pontoperla katherinae Balinsky (Plecoptera, Chloroperlidae) - Zhiltzova, Lidia A. (Illiesia, 2011)
For the first time the larva of P. katherinae from the Caucasus is described. It differs from the larva of P. teberdinica in a more uniformly pigmented body color and in peculiarity of setae on body and cerci.
Keywords: entomologija; entomology; Plecoptera; vrbnice; Chloroperlidae; Pontoperla; Pontoperla katherinae; larval description; Caucasus; larve